Phylogenomic and population genetics analyses of extant tomato yellow leaf curl virus strains on a global scale - Marchant, Wendy G.; Mugerwa, Habibu; Gautam, Saurabh; Al-Aqeel, Hamed; Polston, Jane E.; Rennberger, Gabriel; Smith, Hugh; Turechek, Bill; Adkins, Scott; Brown, Judith K.; Srinivasan, Rajagopalbabu (Frontiers in Virology, 2023)
Tomato yellow leaf curl virus (TYLCV) is a monopartite DNA virus with a genome size of ~ 2,800 base pairs. The virus belongs to the genus Begomovirus within the family Geminiviridae. Extant TYLCV strains are differentiated based on an established threshold of 94% genome-wide pairwise nucleotide identity. The phylogenetic relationships, diversification mechanisms, including recombination, and extent of spread within and from the center of origin for TYLCV have been reported in previous studies. However, the evolutionary relationships among strains, strains' distribution and genomic diversification, and genetic mechanisms shaping TYLCV strains' evolution have not been re-evaluated to consider globally representative genome sequences in publicly available sequence database, including herein newly sequenced genomes from the U.S. and Middle East, respectively. In this study, full-length genome sequences for the extant strains and isolates of TYLCV (n=818) were downloaded from the GenBank database. All previously published genome sequences, and newly sequenced TYLCV genomes of TYLCV isolates from Kuwait and USA, determined herein (n=834), were subjected to recombination analysis. To remove the 'phylogenetic noise' imparted by interspecific recombination, the recombinant genomes were removed from the data set, and the remaining non-recombinant genome sequences (n=423) were subjected to population genetics and Bayesian analyses. Results of the phylogeographical analysis indicated that the type strain, TYLCV-Israel, and TYLCV-Mild strain, were globally distributed, spanning